JARINGAN SYARAF TIRUAN DENGAN ALGORITMA BACKPROPAGATION UNTUK MEMPREDIKSI NILAI UJIAN KOMPETENSI SISWA (STUDI KASUS SMKS JABAL RAHMAH STABAT) - Kiki Sri Handayani; Katen Lumbanbatu; Magdalena Simanjuntak (UNIVERSITAS PEMBANGUNAN PANCA BUDI, 2021)
Competency testing is a process of assessment (assessment) both technical and non-technical through the collection of relevant evidence to determine whether a person is competent or not yet competent in a certain competency unit or job qualification. The implementation of the series of